Sequence-Specific Detection of Aristolochia DNA – A Simple Test for Contamination of Herbal Products - Sgamma, Tiziana; Masiero, Eva; Mali, Purvi; Mahat, Maslinda; Slater, Adrian (Frontiers in Plant Science, 2018)
Herbal medicines are used globally for their health benefits as an alternative therapy method to modern medicines. The market for herbal products has increased rapidly over the last few decades, but this has in turn increased the opportunities for malpractices such as contamination or substitution of products with alternative plant species. In the 1990s, a series of severe renal disease cases were reported in Belgium associated with weight loss treatment, in which the active species Stephania tetrandra was found to be substituted with Aristolochia fangchi. A. fangchi contains toxic aristolochic acids, which have been linked to kidney failure, as well as cancers of the urinary tract. Because of these known toxicities, herbal medicines containing these compounds, or potentially contaminated by these plants, have been restricted or banned in some countries, but they are still available via the internet and in alternate formulations. In this study, a DNA based method based on quantitative real-time PCR (qPCR) was tested to detect and distinguish Aristolochia subg. Siphisia (Duch.) O.C.Schmidt species from a range of medicinal plants that could potentially be contaminated with Aristolochia material. Specific primers were designed to confirm that Aristolochia subg. Siphisia can be detected, even in small amounts, if it is present in the products, fulfilling the aim of offering a simple, cheaper and faster solution than the chemical methods. A synthetic gBlock template containing the primer sequences was used as a reference standard to calibrate the qPCR assay and to estimate the copy number of a target gene per sample. Generic primers covering the conserved 5.8S rRNA coding region were used as internal control to verify DNA quality and also as a reference gene for relative quantitation. To cope with potentially degraded DNA, all qPCR primer sets were designed to generate PCR products of under 100 bp allowing detection and quantification of A. fangchi gBlock even when mixed with S. tetrandra gBlock in different ratios. All proportions of Aristolochia, from 100 to 2%, were detected. Using standards, associating the copy number to each start quantity, the detection limit was calculated and set to about 50 copies.